Relating structural loading rate to tensing rate for fracture mechanics specimens: - Walters, C.L.; Przydatek, J. (2014)
It is vely well-known that fracture toughness depends on loading rate. Higher strain rates can shift the ductile to brittle transition curve to higher temperatures, resulting in a more brittle structure at the same temperature. However, there is little effort to relate the testing rate to the loading rate within the offshore and maritime industry. For example, BS 7448-l requires that the stress intensity factor loading rate be 0.5 MPalVm/s to 3.0 MPaVim/s. The loading rates of BS 7448-l are very far away from the vibrational modes of the specimen, so these limitations are not necessary in order to assure a quasistatic test. In comparison, SSC 275 indicates that normal ship loading rates can be of the order of 220-440WPaVm/s. The results of SSC 275 are consistent with results obtained from a Dutch oflshore equipment supplier, who indicates a time to maximum loading of 0.25- 1.3 seconds. In general, a conservative loading scenario for the maritime and offshore industry is on the order of 200 times faster than the loading rate that is recommended by BS 7448-1. Testing at the standard rate has the consequence of artificially lowering the ductile to brittle transition temperature by 8-35°C in comparison to a real loading scenario, thus possibly giving a false impression of safety. This means that a CTOD measured as 0.2 mm for static testing conditions could be 0.08-0.15 mm for actual loading. The analysis is shown to be consistent with CTOD test data on a Quenched and Tempered (QT) and a Thelmo-Mechanically Controlled Processed (TMCP) 5690 grade steel